Digital development and economic growth in selected ASEAN countries: applying response surfaces for critical bounds of cointegration test - Duasa, Jarita; Ramadan, Aisha Elalim (University Malaya, 2019)
The study attempts to analyse the relationship between digital development and economic growth in selected ASEAN economies using small sample data. Using bound testing technique of cointegration, the new critical values of the test are recalculated to fit for small sample data of each country based on response surface in order to obtain rigorous results without ignoring the individual country analysis. The results show that long-run positive impact of digital transformation on economic growth is profound in Malaysia and the Philippines. However, in short-run, most countries in the region, regardless of income level or economic development, encountered negative implication of digital transformation on growth due to digital divide caused by the diversity of the member countries of ASEAN that might affect the accessibility and connectivity of network in the process of transformation.